2017
DOI: 10.1002/lary.26579
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomes of the normal middle ear and ears with chronic otitis media

Abstract: 2b. Laryngoscope, 127:E371-E377, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 25 publications
3
39
0
3
Order By: Relevance
“…In the microbiota of MEF, Alloiococcus appears to be one of the dominant genera (Jervis- Bardy et al, 2015;Chan et al, 2016Chan et al, , 2017bBoers et al, 2018;Lappan et al, 2018;Val et al, 2018;Johnston et al, 2019). Turicella is less often reported, but has been identified as a member of the MEF microbiota in 8 of the 12 MEF microbiota studies reported in Table 3 (Jervis- Bardy et al, 2015;Krueger et al, 2017;Minami et al, 2017;Sillanpää et al, 2017;Boers et al, 2018;Lappan et al, 2018;Val et al, 2018;Johnston et al, 2019). However, due to the compositional nature of microbiome data it remains difficult to interpret which organisms are more abundant than others.…”
Section: Detection Of a Otitidis And T Otitidis In Mef Has Increasementioning
confidence: 99%
“…In the microbiota of MEF, Alloiococcus appears to be one of the dominant genera (Jervis- Bardy et al, 2015;Chan et al, 2016Chan et al, , 2017bBoers et al, 2018;Lappan et al, 2018;Val et al, 2018;Johnston et al, 2019). Turicella is less often reported, but has been identified as a member of the MEF microbiota in 8 of the 12 MEF microbiota studies reported in Table 3 (Jervis- Bardy et al, 2015;Krueger et al, 2017;Minami et al, 2017;Sillanpää et al, 2017;Boers et al, 2018;Lappan et al, 2018;Val et al, 2018;Johnston et al, 2019). However, due to the compositional nature of microbiome data it remains difficult to interpret which organisms are more abundant than others.…”
Section: Detection Of a Otitidis And T Otitidis In Mef Has Increasementioning
confidence: 99%
“…Several studies [17][18][19][20] have attempted to test if the otic mucosa of healthy individuals is indeed free of bacteria, albeit results thus far have been inconclusive. Its secluded location behind the eardrum motivated studies that collected samples as part of transcanal surgical procedures designed to treat a number of otic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive optical techniques also detected signals from bacterial biofilms in the middle ear of patients with a history of chronic ear infections but not in uninfected controls [22]. To improve the sensitivity of the detection method, Minami et al [19] used transcanal surgery to collect middle ear mucosal swabs from pediatric and adult patients with or without a history of chronic ear infections. The detection in all the samples of a phylogenetically diverse pool of 16S rRNA amplicon sequences supported the conclusion that "the human middle ear is inhabited by more diverse microbial communities than was previously thought" [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations